An Inventory Model for Deteriorating Items With Exponential Declining Demand and Return - Fadli Fadli; Sudarajat Sudrajat; E. Lesmana (Sam Ratulangi University, 2020)
In this paper propose an EOQ mathematical model for deteriorating items. The model is developed with a demand function that decreases exponentially, a constant deterioration rate, a shortage is permitted, and a return occurs. The purpose of this model is to determine the minimum total cost by determining the optimal return time and the optimal number of orders. A numerical example is given to describe the working model. Furthermore, a sensitivity analysis was conducted to see the effect of changing parameters on the optimal solution.Keywords: Deteriorating item, inventory, return, shortageModel Persediaan Deteriorasi Item Dengan Exponential Declining Demand dan ReturnABSTRAKDalam makalah ini mengusulkan model matematika EOQ untuk item yang mengalami deteriorasi. Model ini dikembangkan dengan fungsi permintaan yang menurun secara eksponensial, laju deteriorasi konstan, kekurangan diizinkan, dan terjadi pengembalian. Tujuan dari model ini adalah untuk menentukan biaya total minimum dengan menentukan waktu pengembalian optimal dan jumlah pesanan optimal. Contoh numerik diberikan untuk menggambarkan model bekerja. Selanjutnya, analisis sensitivitas dilakukan untuk melihat efek perubahan parameter pada solusi optimal.Kata kunci: Deteriorasi item, persediaan, pengembalian, kekurangan